2020
DOI: 10.3389/fphys.2020.00291
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation and Perfusion at the Alveolar Level: Insights From Lung Intravital Microscopy

Abstract: Intravital microscopy (IVM) offers unique possibilities for the observation of biological processes and disease related mechanisms in vivo. Especially for anatomically complex and dynamic organs such as the lung and its main functional unit, the alveolus, IVM provides exclusive advantages in terms of spatial and temporal resolution. By the use of lung windows, which have advanced and improved over time, direct access to the lung surface is provided. In this review we will discuss two main topics, namely alveol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 103 publications
(163 reference statements)
0
14
0
Order By: Relevance
“…However, the effects of artificial ventilation on lung physiology must be acknowledged (Poobalasingam et al, 2017 ). Manipulations in mechanics of the thoracic wall and the interplay between intrapleural and transpulmonary pressures impact both alveolar dynamics and microvascular perfusion (Tabuchi et al, 2020 ). Therefore, although mechanical ventilation is essential for survival of the animal, it can cause permanent damage to the lung as ventilator induced lung injury (VILI) or ventilator-associated lung injury (VALI) (Amato et al, 1998 ).…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the effects of artificial ventilation on lung physiology must be acknowledged (Poobalasingam et al, 2017 ). Manipulations in mechanics of the thoracic wall and the interplay between intrapleural and transpulmonary pressures impact both alveolar dynamics and microvascular perfusion (Tabuchi et al, 2020 ). Therefore, although mechanical ventilation is essential for survival of the animal, it can cause permanent damage to the lung as ventilator induced lung injury (VILI) or ventilator-associated lung injury (VALI) (Amato et al, 1998 ).…”
Section: Limitationsmentioning
confidence: 99%
“…However, it has been reported that certain lung windows may allow for long-term observations in dogs, rabbits (De Alva and Rainer, 1963 ), rats (Fingar et al, 1994 ) or mice (Kimura et al, 2010 ), without stabilization and at low spatial resolution. Entenberg et al recently developed a permanent lung window which may present a promising method for long-term imaging (Entenberg et al, 2018 ; Tabuchi et al, 2020 ).…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pulmonary surfactant system plays a critical role in reducing end-expiratory surface tension at the alveolar air–liquid interface as well as in minimizing respiratory workload during inspiration (Bachofen and Schürch 2001 ). These physiological functions are essential for alveolar micromechanics, defined as the morphological changes of alveoli during the respiratory cycle (Matuszak et al 2020 ). The surface tension-lowering properties of surfactant stabilize alveolar dimensions even at low lung volumes so that the gas exchange surface area remains stable.…”
Section: Introductionmentioning
confidence: 99%